Amnesty as a tool of transitional justice : the South African Truth and Reconciliation Commission in profile - Viljoen, Frans (University of Pretoria, 2006)
Prepared under the supervision of Professor Frans Viljoen, Faculty of Law, University of Pretoria, South Africa